Effects of Zumba® and Aquagym on Bone Mass in Inactive Middle-Aged Women - Esther Ubago-Guisado; Javier Sánchez-Sánchez; Sara Vila-Maldonado; Leonor Gallardo (Medicina, 2019)
Background and objectives: Regular exercise may stimulate bone formation and reduce the loss of bone mass in premenopausal women. This study aims to evaluate the effect of high-impact physical activity (Zumba®) and low-impact physical activity (Aquagym) on bone mass in inactive middle-aged women. Materials and methods: Fifty-five healthy inactive women (30⁻50 years old) were recruited in Spain in 2016 and were randomly allocated into one of three groups: High impact group (HIG: n = 15), low impact group (LIG: n = 12) and control group (CG: n = 28). HIG and LIG were recruited from Madrid and the CG from Toledo. HIG and LIG completed a 12-week intervention program with three 40′ sessions per week of Zumba® or Aquagym; respectively. Dual energy X-ray absorptiometry (DXA) measured bone mineral content (BMC) and areal bone mineral density (aBMD) at total body less head (TBLH), lumbar spine and right hip. Results: Post-intervention adjusted data showed no significant differences in BMC between any of the groups nor in aBMD between HIG and LIG. Interestingly; significant differences for the HIG vs. CG were found in the change in total hip aBMD (1.76% vs. −0.44%), femoral neck aBMD (1.80% vs. −2.71%), and intertrochanter aBMD (2.03% vs. −0.50%). Moreover, significant differences for the LIG vs. CG were also found in the change in femoral neck aBMD (−0.54% vs. −2.71%). Conclusions: The regular practice of Zumba® and Aquagym might reduce the progressive deterioration of bone mass in inactive middle-aged women